(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the vital and ethical foundations of environmental stewardship. The research emphasizes the necessity of perceiving nature not merely as a resource for human consumption but as a complex living system. Drawing upon the ecological roles of flora, the study explains the ethical and scientific dimensions of environmental protection, supported by the philosophical insights of both ancient and modern scholars. Ultimately, the paper calls for a reassessment of humanity's responsibility to live in harmony with the natural world.(3)